Non-Vertebral Fracture Reduction with High- vs Low-Dose Ibandronate - Vinall, Phil (MD Conference Express, 2007)
Results from the Oral IBandronate Osteoporosis Vertebral Fracture Trial in North America and Europe [BONE] study showed a significant (p=0.0001) 62% reduction in the risk of vertebral fractures in women with postmenopausal osteoporosis treated with oral ibandronate, either as 2.5 mg daily or as 20 mg every other day for 12 doses every 3 months [Chesnut CH et al. Bone Miner Res 2004].